A comparison between political claims analysis and discourse network analysis: The case of software patents in the European Union - Philip Leifeld; Sebastian Haunss (Max Planck Institute for Research on Collective Goods, 2010)
The study of policy discourse comprises actor-centered and content-oriented approaches. We attempt to close the gap between the two kinds of approaches by introducing a new methodology for the analysis of political discourse called Discourse Network Analysis. It is based on social network analysis and qualitative content analysis and takes an entirely relational perspective. Political discourse can be analyzed in a dynamic way, and the approach makes previously unobservable cleavage lines and alignments measurable at the actor level, at the level of the contents of a discourse, and a combined layer. We compare discourse network analysis with political claims analysis, a competing method, and apply both methods to the European-level discourse on software patents. Our results demonstrate how an anti-softwarepatent coalition was mobilized and how it gained control over important frames, while the well-organized pro-software-patent discourse coalition was not able to gain sovereignty over the discourse.
Keywords: 330; Software Patents; Intellectual Property Rights; Discourse Network Analysis; Social Network Analysis; Political Discourse; Policy Networks; Public Policy Analysis; Social Movements; Political Claims Analysis; EU-Politik; Diskursanalyse; Soziales Netzwerk; Interessenpolitik; Software-Recht; Patentrecht; EU-Staaten